The Potential of Brewer’s Spent Grain in the Circular Bioeconomy: State of the Art and Future Perspectives - Zeko-Pivač, Anđela; Tišma, Marina; Žnidaršič-Plazl, Polona; Kulisic, Biljana; Sakellaris, George; Hao, Jian; Planinić, Mirela (Frontiers in Bioengineering and Biotechnology, 2022)
Graphical Abstract